Narrowband Emissive Thermally Activated Delayed Fluorescence Materials - Kim, Hyung Jong; Yasuda, Takuma (Advanced optical materials, 2022)
Organic thermally activated delayed fluorescence (TADF) materials have attracted significant research interest in the field of organic electronics because of their inherent advantage of 100% exciton utilization capability in organic light‐emitting diodes (OLEDs) without the use of noble metals. However, despite their high internal electroluminescence quantum efficiencies approaching unity, broad emission spectra with sizable full width at half maxima (FWHM; 60–100 nm) present a critical issue that must be solved for their application in ultrahigh‐definition OLED displays. Recently, a new paradigm of TADF materials featuring the multiple resonance (MR) effect based on heteroatom‐doped polycyclic aromatic frameworks, referred to as MR‐TADF materials, has emerged and garnered considerable research interest owing to their remarkable features of efficient narrowband emissions with extremely small FWHMs (≤30 nm). Currently, MR‐TADF materials occupy a prominent position in the cutting‐edge research on organic light‐emitting materials from both chemical and physical perspectives. This review article focuses on recent progress in narrowband emissive MR‐TADF systems from the perspective of molecular design, photophysical properties, and electroluminescence performance in OLEDs. The current status and future prospects of this advanced material technology are discussed comprehensively. Organoboron‐based thermally activated delayed fluorescence (TADF) materials that enable high‐efficiency and high‐color‐purity electroluminescence are actively researched in recent years. This review focuses on recent advances in narrowband emissive TADF materials with spectral full width at half maxima narrower than 50 nm, from the perspective of molecular design strategies, photophysical properties, and electroluminescence performance in organic light‐emitting diodes.